2002
DOI: 10.1007/s00240-001-0231-4
|View full text |Cite
|
Sign up to set email alerts
|

In vitro comparison of transurethral vaporization of the prostate (TUVP), resection of the prostate (TURP), and vaporization-resection of the prostate (TUVRP)

Abstract: These results allow quantification of the influence of different variables on TUVP, TUVRP, and TURP in vitro. The TUVP proves to be an effective ablation alternative. Nevertheless, a 15 to 20 times higher energy demand has to be considered. TUVRP combines excellent ablation features with greater coagulation volumes, indicating better hemostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In addition, the authors found a remarkable decline in tissue removal of more than 50% for TUVP on pretreated tissue, which can only be compensated in vivo by an additional energy input. Compared to standard TURP, pure electrovaporization as done in this particular patient requires slower speed, higher voltage, and increased pressure application [11]. In this case, the second surgery in February 2016 was of 55 minutes’ duration, which was 10 minutes longer than the initial TURP in 2011.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, the authors found a remarkable decline in tissue removal of more than 50% for TUVP on pretreated tissue, which can only be compensated in vivo by an additional energy input. Compared to standard TURP, pure electrovaporization as done in this particular patient requires slower speed, higher voltage, and increased pressure application [11]. In this case, the second surgery in February 2016 was of 55 minutes’ duration, which was 10 minutes longer than the initial TURP in 2011.…”
Section: Discussionmentioning
confidence: 98%
“…[11]. They reported a 15 to 20 times higher energy demand to be considered when applying the vaporization technique in order to achieve comparable results to conventional TURP.…”
Section: Discussionmentioning
confidence: 99%
“…A similar process of tissue vaporisation is involved in transurethral electrovapor resection of the prostate (TUVRP), which uses a thick wedge loop allowing for simultaneous vaporisation and resection of the gland, and is responsible for approximately 50% resected tissue weight reduction [ 17 , 18 ], whereas the loss of glandular mass that occurs in EVAP is strictly due to tissue vaporisation.…”
Section: Introductionmentioning
confidence: 99%